Awareness on the impact of instant noodles consumptions among undergraduate Students In Health Campus, USM - Ameran, Nur Aqilah (Universiti Sains Malaysia, 2016)
Instant noodle is a highly processed food that lacks nutritive value. It had consumed by people nowadays due to reasonable price, tasty and easy to serve. Instant noodle consumption become rise and it also have the impact on health. The aim of this study was to determine the prevalence and awareness level on the impact of instant noodles consumption among undergraduate students in health campus, USM. A cross-sectional design was used in this study. Two hundred thirty two (232) students were recruited in this study by cluster random sampling of undergraduate students in health campus, USM from January until February 2016. A self-administered questionnaire was used to collect data. Data was analysed using the Statistical Package for the Social Sciences (SPSS) version 22.0 for windows and Stata software 13. Pearson Chi Square, Fisher’s Exact Test and One-way Anova analyses were conducted to explore the association between socio-demographic characteristic, health history and instant noodles consumption. A p value < 0.05 was considered statistically significant. One hundred twenty six respondents (54.3%) reported rare instant noodles consumption with moderate (mean=3.94) awareness level on the impact of instant noodle. 142 of respondent were categorized in normal body mass index (BMI), 20.3% of respondent underweight and 3.4% of respondent were obese. There was a significant association between gender and parental attention with prevalence of instant noodles consumption. Burning sensation on stomach (23.7%), bloating and irregular bowel movement (23.3%) and headache (18.1%) were the symptoms presented by respondents after consumed instant noodle. This study revealed the prevalence and awareness on the impact instant noodles consumption among students in health campus was moderate. The findings of the present study indicate a need for health education and promotion on impact of instant noodle to health and healthy nutrition to improve understanding about impact of instant noodles to health committee and public